A process for preparing polyaluminium-iron silicate flocculant and co-producing white carbon black from red mud

By using low-temperature acid leach and surfactant regulation methods in the red mud preparation process, the problems of elements separation and purification in red mud are solved, and efficient resource recycling of iron, aluminum and silicon elements in red mud are achieved. The process is short and the energy consumption is low, and it is suitable for the preparation of multi-element products.

CN116161757BActive Publication Date: 2025-05-02SHANXI UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211563495.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-07
Publication Date
2025-05-02
Estimated Expiration
2042-12-07

AI Technical Summary

Technical Problem

The problem of separation and purification of elements in red mud is that the existing process flow is long and the process of removing impurities is cumbersome, which makes it difficult to achieve efficient resource recycling of aluminum, iron, silicon and other elements in red mud.

Method used

By controlling the low-temperature acid leaching process of red mud, the presence form of silicon in the leaching system is changed, and the desilication is regulated by surfactant, excess silicon is separated to prepare white carbon black, and at the same time, the alkalinization of the acid leaching liquid is adjusted to obtain polymeric ferrous aluminum silicate flocculant.

Benefits of technology

It realizes synchronous and efficient dissolution and resource recycling of iron, aluminum and silicon elements in red mud. The process flow is short, energy consumption is low, equipment requirements are low, and product application range is wide.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116161757B_ABST
    Figure CN116161757B_ABST
Patent Text Reader

Abstract

The purpose of the present invention is to provide a process for preparing polysilicate aluminum iron flocculant and co-producing white carbon black from red mud, which belongs to the technical field of solid waste resource utilization. The process flow is as follows: red mud is roasted and activated at a certain temperature, the roasted clinker is mixed with hydrochloric acid or sulfuric acid at a specific liquid-solid ratio, acid leaching and dissolving are carried out within the room temperature range, and solid-liquid separation is performed to obtain acid leaching solution 1 and titanium-rich slag; surfactant (hexadecyltrimethylammonium bromide, polyethylene glycol) is added to the acid leaching solution 1 for precipitation and desiliconization, and solid-liquid separation is performed to obtain acid leaching solution 2 and white carbon black; an alkalizer (such as sodium hydroxide, sodium carbonate) is added to the acid leaching solution 2, and a polysilicate aluminum iron flocculant product is obtained through polymerization reaction. The process flow is short and the reaction conditions are mild. The polysilicate aluminum iron flocculant product is prepared by room temperature dissolution and acid leaching solution alkalinity adjustment, and the resource utilization of aluminum, iron and silicon in red mud can be realized at the same time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of solid waste resource utilization, and specifically relates to a process for preparing polyaluminium-iron silicate flocculant and co-producing white carbon black from red mud. Background Art

[0002] Red mud is the waste residue discharged during the production of alumina. It is red in color due to its high iron oxide content, so it is called red mud. At present, the disposal method of red mud in my country is mostly storage and damming, which not only occupies a large amount of land and consumes a lot of maintenance costs, but also its strong alkalinity seriously damages the ecological environment. However, red mud contains a variety of valuable metals such as aluminum, iron, silicon, titanium, calcium, and magnesium. It is a usable secondary resource that can be used to extract valuable metals and to prepare building materials and environmental materials. In particular, red mud is rich in aluminum, iron, and silicon, so element recovery has become an important way to utilize red mud resources.

[0003] Red mud can be used to recover iron, aluminum, silicon and other elements to prepare a series of products (such as iron concentrate, alumina, white carbon black, flocculants, etc.). However, when using red mud as a raw material to prepare these products containing single or two elements, it is usually faced with the problem of element separation and purification in red mud. Based on the chemical composition characteristics of red mud, using it as a raw material for the preparation of multi-element products is a more suitable way to recover elements. Polysilicate aluminum iron (PSAF) is a new type of water treatment flocculant composed of silicon, aluminum and iron. Compared with traditional water treatment flocculants (such as polyaluminium chloride, polyferric chloride, polyaluminium ferric chloride, etc.), it has the advantages of fast polymerization speed and obvious flocculation effect of aluminium salt flocculants, dense flocs and fast sedimentation speed of iron salt flocculants, and strong adhesion aggregation ability and adsorption bridging effect of polysilicic acid. It also overcomes some shortcomings of loose and fragile flocs of aluminium salt flocculants, difficulty in complete sedimentation, excessive residual aluminium content, fast hydrolysis speed and poor stability of iron salt flocculants, and easy gelation of polysilicic acid flocculants. It is also increasingly used in the field of water treatment due to its stable product performance. The present invention controls the acid leaching process of activated red mud to be carried out at a low temperature of 15-30°C, effectively changing the existence form of silicon in the leaching system; then, by adding a surfactant to regulate desiliconization, excess silicon is separated for the preparation of white carbon black; finally, by adjusting the alkalinity of the acid leaching solution, a polysilicate aluminium ferric flocculant is further prepared. Summary of the invention

[0004] The purpose of the present invention is to provide a process for preparing polyaluminium-iron silicate flocculant and co-producing white carbon black by using red mud, including roasting activation, low-temperature acid leaching, precipitation desiliconization, alkalization polymerization and the like. By regulating the low-temperature acid leaching conditions of red mud, the simultaneous and efficient dissolution of iron, aluminium and silicon is enhanced, the reaction energy consumption is reduced, so as to achieve the comprehensive recovery of elements such as aluminium, iron and silicon in red mud.

[0005] The present invention adopts the following technical solution:

[0006] A process for preparing polyaluminium-iron silicate flocculant and co-producing white carbon black from red mud comprises the following steps:

[0007] S1. Material pretreatment: Grind and sieve the red mud to less than 100 mesh, and dry it to obtain pretreated material for standby use;

[0008] S2, roasting and activation: placing the pretreated material in an atmosphere furnace, roasting and activating it in an air atmosphere to obtain roasted clinker;

[0009] S3, low temperature acid leaching: the roasted clinker is mixed with the acid solution in proportion, and acid leaching is carried out at room temperature, and solid-liquid separation is performed to obtain acid leaching solution 1 and titanium-rich slag;

[0010] S4, precipitation desiliconization: adding a surfactant to the acid leaching solution 1 at room temperature for precipitation desiliconization, and solid-liquid separation to obtain the acid leaching solution 2 and the white carbon black product;

[0011] S5, alkalization polymerization: add alkalizer to the acid leaching solution 2, and obtain the polysilicate aluminum iron flocculant product through polymerization reaction.

[0012] Furthermore, the red mud described in S1 includes any one of Bayer process red mud, sintering process red mud and combined process red mud.

[0013] Furthermore, the atmosphere in S2 is an air atmosphere; the calcination temperature is 600-900° C., and the calcination time is 1.5-2 h.

[0014] Furthermore, the acid solution in S3 is a 10-25 wt.% hydrochloric acid or sulfuric acid solution; the acid solution is mixed with the roasted clinker at a liquid-solid ratio of 6-8 mL / g, the acid leaching temperature is room temperature 15-30°C, and the acid leaching time is 30-90 min.

[0015] Furthermore, the surfactant in S4 includes hexadecyltrimethylammonium bromide or polyethylene glycol, and the addition amount is 0.9~2.1×10 -3 mol / L or 0.5~2.0×10 -3 mol / L, desiliconization temperature is 15~30℃, and reaction time is 30~60min.

[0016] Furthermore, the alkalizing agent in S5 includes sodium hydroxide, sodium carbonate or calcium aluminate powder, and the concentration of the alkalizing agent is 1.5 mol / L; the polymerization temperature is 75-90° C., and the polymerization time is 60-150 min.

[0017] The present invention proposes a process for preparing polyaluminium ferric silicate flocculant and co-producing white carbon black by using red mud with high efficiency and short process, comprising the steps of grinding and screening red mud and then calcining and activating it in an air atmosphere; acid leaching and dissolving the calcined clinker at room temperature, and solid-liquid separation to obtain an acid leaching solution 1 and titanium-rich slag; adding a surfactant to the acid leaching solution 1 for precipitation and desiliconization, and solid-liquid separation to obtain an acid leaching solution 2 and a white carbon black product; adding an alkalizing agent (such as sodium hydroxide or sodium carbonate) to the acid leaching solution 2, and obtaining a polyaluminium ferric silicate flocculant product through a polymerization reaction.

[0018] The invention proposes a process for preparing polyaluminium-iron silicate flocculant and co-producing white carbon black by using red mud with high efficiency and short process. The process is short, the reaction conditions are mild and the product has a wide application range.

[0019] The beneficial effects of the present invention are as follows:

[0020] The chemical composition of red mud is complex, and the existing multi-element recovery process is long and the impurity removal process is cumbersome. The present invention is based on the simultaneous and efficient dissolution characteristics of iron, aluminum and silicon under low-temperature acid leaching conditions, combined with the regulatory effect of surfactants on the silicon morphology in the acid leaching solution, to achieve the preparation of polyaluminum-iron silicate flocculant and co-production of white carbon black from red mud. The process is simple, energy-efficient, and has low requirements for high temperature and corrosion resistance of equipment, and can achieve efficient resource recovery of iron, aluminum and silicon elements in red mud. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 The process flow chart of preparing polyaluminium-iron silicate flocculant and co-producing white carbon black from red mud of the present invention;

[0022] Figure 2 This is the product picture of polyaluminium ferric silicate flocculant and white carbon black;

[0023] Figure 3 is the yield and purity of white carbon black product;

[0024] Figure 4 This is the removal efficiency diagram of polyaluminium ferric silicate flocculant for chroma and COD of domestic sewage. DETAILED DESCRIPTION

[0025] The present invention will be described in detail below in conjunction with the specific implementation methods and embodiments of the present invention, and the advantages and various effects of the present invention will be more clearly presented. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0026] The red mud used in the embodiments of the present invention was taken from Shanxi Aluminum Co., Ltd., Xinzhou State Power Investment Group, Shanxi Province. The chemical composition analysis of the red mud raw material is shown in Table 1 below:

[0027] Table 1 Chemical composition of red mud (%)

[0028]

[0029] Example 1

[0030] A process for preparing polyaluminium ferrosilicate flocculant and co-producing white carbon black by using red mud, the process flow is as follows: Figure 1 As shown in the figure, the specific method is as follows: the above red mud is ground and sieved to less than 100 mesh, and then the material is placed in an air atmosphere furnace after drying and roasted at 600℃ for 2 h; 15 wt.% hydrochloric acid solution is mixed with the roasted clinker at a liquid-solid ratio of 6mL / g, and acid leaching is performed at 30℃ for 90 min, and solid-liquid separation is performed to obtain acid leaching solution 1; then hexadecyl trimethyl ammonium bromide is added to the acid leaching solution 1 at a concentration of 9×10 -4 mol / L, stirred at 30℃ for 30 min, solid-liquid separation to obtain acid leaching solution 2 and white carbon black product, white carbon black yield of 70%, purity of 90%; add alkalizing agent NaOH to acid leaching solution 2, concentration of 1.5 mol / L, polymerization reaction at 75℃ for 60 min, stand for aging for 4 h, solid-liquid separation to obtain polysilicate aluminum iron flocculant product. The flocculant (Al+Fe) / Si molar ratio is 12:1, and the removal rates of chromaticity and COD of domestic sewage are 76% and 56% respectively when the dosage is 200 mg / L.

[0031] Example 2

[0032] The red mud was ground and sieved to less than 100 mesh. After drying, the material was placed in an air atmosphere furnace and roasted at 700 °C for 1.5 h. 10 wt.% hydrochloric acid solution was mixed with the roasted clinker at a liquid-solid ratio of 6 mL / g, and acid leaching was performed at 20 °C for 60 min. The solid-liquid separation obtained an acid leaching solution 1. Then, 1.3×10 hexadecyltrimethylammonium bromide was added to the acid leaching solution 1. -3 mol / L, stirred and reacted at 20℃ for 60 min, and obtained acid leaching solution 2 and white carbon black product, with white carbon black yield of 68% and purity of 93%; added alkalizing agent NaOH with a concentration of 1.5 mol / L to acid leaching solution 2, polymerized at 85℃ for 90 min, left to stand for 4 h, and obtained polysilicate aluminum iron flocculant product after solid-liquid separation. The flocculant (Al+Fe) / Si molar ratio was 13:1, and the removal rates of chromaticity and COD of domestic sewage reached 80% and 58% respectively when the dosage was 200 mg / L.

[0033] Example 3

[0034] The red mud was ground and sieved to less than 100 mesh. After drying, the material was placed in an oxygen-enriched atmosphere furnace and roasted at 800 °C for 1.5 h. 20 wt.% hydrochloric acid solution was mixed with the roasted clinker at a liquid-solid ratio of 7 mL / g, and acid-leached at 15 °C for 60 min. The solid-liquid separation obtained acid solution 1. Then, 5.0×10 -2 mol / L, stirred and reacted at 15℃ for 60min, and obtained acid leaching solution 2 and white carbon black product, with white carbon black yield of 72% and purity of 94%; added alkalizing agent NaOH to acid leaching solution 2 at a concentration of 1.5 mol / L, polymerized at 90℃ for 120min, left to stand for 4h, and obtained polysilicate aluminum iron flocculant product after solid-liquid separation. The flocculant (Al+Fe) / Si molar ratio was 10:1, and the removal rates of chromaticity and COD of domestic sewage reached 70% and 50% respectively when the dosage was 200 mg / L.

[0035] Example 4

[0036] The red mud was ground and sieved to less than 100 mesh. After drying, the material was placed in an oxygen-enriched atmosphere furnace and roasted at 850 °C for 1.5 h. 10 wt.% hydrochloric acid solution was mixed with the roasted clinker at a liquid-solid ratio of 8 mL / g, and acid-leached at 20 °C for 90 min. The solid-liquid separation obtained acid solution 1. Then, 1.5×10 -3 mol / L, stirred and reacted at 15℃ for 60min, and obtained acid leaching solution 2 and white carbon black product, with white carbon black yield of 67% and purity of 90%; added alkalizing agent NaOH to acid leaching solution 2 at a concentration of 1.5 mol / L, polymerized at 80℃ for 150min, left to stand for aging for 4h, and obtained polysilicate aluminum iron flocculant product after solid-liquid separation. The flocculant (Al+Fe) / Si molar ratio was 14:1, and the removal rates of chromaticity and COD of domestic sewage reached 79% and 58% respectively when the dosage was 200 mg / L.

[0037] Example 5

[0038] The red mud was ground and sieved to less than 100 mesh. After drying, the material was placed in an oxygen-enriched atmosphere furnace and roasted at 900 °C for 1.5 h. 15 wt.% hydrochloric acid solution was mixed with the roasted clinker at a liquid-solid ratio of 8 mL / g, and acid-leached at 15 °C for 30 min. After solid-liquid separation, an acid leaching solution 1 was obtained. Subsequently, 9×10 hexadecyltrimethylammonium bromide was added to the acid leaching solution 1. -4 mol / L, polyethylene glycol 1.0×10 -3mol / L, stirred and reacted at 20℃ for 30 min, and obtained acid leaching solution 2 and white carbon black product, with white carbon black yield of 72% and purity of 93%; added alkalizing agent NaOH to acid leaching solution 2 at a concentration of 1.5 mol / L, polymerized at 80℃ for 150 min, left to stand for 4 h, and obtained polysilicate aluminum iron flocculant product after solid-liquid separation. The molar ratio of flocculant (Al+Fe) / Si was 15:1, and the removal rates of chromaticity and COD of domestic sewage reached 78% and 56% respectively when the dosage was 200 mg / L.

Claims

1. A process for preparing polyaluminium ferrosilicate flocculant and co-producing white carbon black from red mud, characterized in that: The steps include: S1. Material pretreatment: Grind and sieve the red mud to less than 100 mesh, and dry it to obtain pretreated material for standby use; S2, roasting and activation: placing the pretreated material in an atmosphere furnace, roasting and activating it in an air atmosphere to obtain roasted clinker; S3, low temperature acid leaching: the roasted clinker is mixed with the acid solution in proportion, and acid leaching is carried out at room temperature, and solid-liquid separation is performed to obtain acid leaching solution 1 and titanium-rich slag; S4, precipitation desiliconization: adding a surfactant to the acid leaching solution 1 at room temperature for precipitation desiliconization, and solid-liquid separation to obtain the acid leaching solution 2 and the white carbon black product; S5, alkalization polymerization: add alkalizing agent to the acid leaching solution 2, and obtain the polyaluminum ferrosilicate flocculant product through polymerization reaction.

2. The process for preparing polyaluminium ferrosilicate flocculant and co-producing white carbon black from red mud according to claim 1, characterized in that: The red mud described in S1 includes any one of Bayer process red mud, sintering process red mud and combined process red mud.

3. The process for preparing polyaluminium ferrosilicate flocculant and co-producing white carbon black from red mud according to claim 1, characterized in that: The atmosphere described in S2 is air atmosphere; the calcination temperature is 600~900℃, and the calcination time is 1.5~2 h.

4. The process for preparing polyaluminium ferrosilicate flocculant and co-producing white carbon black from red mud according to claim 1, characterized in that: The acid solution in S3 is a 10~25 wt.% hydrochloric acid or sulfuric acid solution; the acid solution is mixed with the roasted clinker at a liquid-to-solid ratio of 6~8mL / g, the acid leaching temperature is room temperature 15~30℃, and the acid leaching time is 30~90 min.

5. The process for preparing polyaluminium ferrosilicate flocculant and co-producing white carbon black from red mud according to claim 1, characterized in that: The surfactant in S4 includes hexadecyltrimethylammonium bromide or polyethylene glycol, and the addition amount is 0.9~2.1×10 -3 mol / L or 0.5~2.0×10 -3 mol / L, desiliconization temperature is 15~30℃, and reaction time is 30~60 min.

6. The process for preparing polyaluminium ferrosilicate flocculant and co-producing white carbon black from red mud according to claim 1, characterized in that: The alkalizing agent in S5 includes sodium hydroxide, sodium carbonate or calcium aluminate powder, and the concentration of the alkalizing agent is 1.5 mol / L; the polymerization temperature is 75-90° C., and the polymerization time is 60-150 min.

Citation Information

Patent Citations

  • Method for preparing nanometer silicon dioxide through taking alkali type activated sludge carbon as raw material

    CN102502661A

  • Comprehensive extraction method of ferro-silico-aluminum in gangue

    CN102515279A